Polysaccharide aggregation as a potential sink of marine dissolved organic carbon - Engel, Anja; Thoms, Silke; Riebesell, Ulf; Rochelle-Newall, Emma; Zondervan, Ingrid (Nature (London), 2004)
The formation and sinking of biogenic particles mediate vertical mass fluxes and drive elemental cycling in the ocean 1 . Whereas marine sciences have focused primarily on particle production by phytoplankton growth, particle formation by the assembly of organic macromolecules has almost been neglected 2 , 3 . Here we show, by means of a combined experimental and modelling study, that the formation of polysaccharide particles is an important pathway to convert dissolved into particulate organic carbon during phytoplankton blooms, and can be described in terms of aggregation kinetics. Our findings suggest that aggregation processes in the ocean cascade from the molecular scale up to the size of fast-settling particles, and give new insights into the cycling and export of biogeochemical key elements such as carbon, iron and thorium.